Challenges in Pronouncing English Consonant Fricatives: Insights from Indonesian EFL Learners - Ristati, Ristati; Bahing, Bahing; Retsi, Olga Dona; Haryani, Tutik; Amalia, Novika (Universitas Muhammadiyah Mataram, 2024)
This study investigates the pronunciation challenges Indonesian EFL learners face with English consonant fricatives. The research aimed to identify common pronunciation errors, explore underlying causes, and propose strategies for improvement. Using an explanatory sequential design, 30 undergraduate students completed a pronunciation test focusing on fricatives, followed by interviews with 10 students who made the most errors. The analysis revealed frequent mispronunciations of fricatives such as /ʒ/, /v/, and /θ/, often substituted with native sounds like /s/, /z/, and /t/. Voiced fricatives posed greater difficulties than voiceless ones, especially in contexts where Indonesian has no phonetic equivalent. Interviews highlighted a lack of familiarity with these sounds and insufficient pronunciation training as primary challenges. Native language interference and limited exposure to correct English pronunciation were significant factors in these difficulties. The findings call for more targeted instruction in English fricatives within the Indonesian EFL context. Further research with larger sample sizes and longitudinal approaches is recommended to explore long-term outcomes.